2021
DOI: 10.1038/s41586-021-03357-x
|View full text |Cite
|
Sign up to set email alerts
|

Breast tumours maintain a reservoir of subclonal diversity during expansion

Abstract: Summary Our knowledge of copy number evolution during the expansion of primary breast tumors is limited 1 , 2 . To investigate this process, we developed a single cell, single-molecule DNA sequencing method and performed copy number analysis of 16,178 single cells from 8 triple-negative breast cancers (TNBCs) and 4 cell lines. Our data shows that breast tumors and cell lines are comprised of a large milieu of subclones (7–22) that are organized i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
229
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 182 publications
(269 citation statements)
references
References 63 publications
(83 reference statements)
16
229
0
Order By: Relevance
“…This confirmed that the SHscore captures the evolutionary history of the tumor subsamples. We used our score to analyze three real scDNA datasets, reaching conclusions in agreement with state of the art phylogenetic approaches [ 39 ] and the original papers [ 55 , 58 ] that presented them. Finally we conducted a downsampling experiment on two cell line data to demonstrate that the SHscore is robust to sample cardinality and may be used in on unbalanced sets.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…This confirmed that the SHscore captures the evolutionary history of the tumor subsamples. We used our score to analyze three real scDNA datasets, reaching conclusions in agreement with state of the art phylogenetic approaches [ 39 ] and the original papers [ 55 , 58 ] that presented them. Finally we conducted a downsampling experiment on two cell line data to demonstrate that the SHscore is robust to sample cardinality and may be used in on unbalanced sets.…”
Section: Discussionmentioning
confidence: 65%
“…In details, we exploited a single-cell dataset, recently published by Minussi et al [ 58 ] on NCBI Sequence Read Archive (accession number PRJNA629885), containing the sequencing reads of cells from a triple-negative breast cancer cell line (MDA-MB-231) (508 cells) and those resulting from the clonal expansion of 2 single daughter cells (MDA231-EX1 and MDA231-EX2) from the parental cell line for 19 cell doublings (995 and 897 cells, respectively). From the sequencing reads, aligned to the GRCh38 reference genome, we called the CNA events using Ginkgo [ 34 ] (additional details on the alignment and CNA calling procedures are available at Supplementary Material: Supplementary Method 1).…”
Section: Resultsmentioning
confidence: 99%
“…Applying this approach across cell types, genetic backgrounds, and experimental conditions will reveal how replication is altered at the spatiotemporal levels in different physiological contexts. With constantly improving methods for high-throughput single cell isolation and accurate whole-genome amplification 18,19,30 , this approach promises to become ever more informative for the understanding of the DNA replication timing program.…”
Section: Methodsmentioning
confidence: 99%
“…Previous sequencing-based studies measured DNA replication timing in a relatively small number of cells, mostly limited to mid-S phase cells 15,16 . To analyze single cells, these studies performed DNA amplification using DOP-PCR, which is known to yield suboptimal DNA copy number measurements 18,19 . Consequently, these studies were limited to analyzing replication timing at the level of large chromosomal domains (typically on the order of megabases).…”
Section: A High-throughput High-resolution Approach For Single Cell Replication Timing Measurementmentioning
confidence: 99%
“…Hence, ERα-positive tumors are highly heterogeneous with a broad range of ERα expression spanning from 1% to nearly 100%. In addition, they display an important intratumoral heterogeneity, as highlighted by a recent work using imaging mass cytometry at the single cell level [242,243].…”
Section: Erα-positive Luminal Breast Cancersmentioning
confidence: 99%